Compression apparel does not have an acute effect on quadriceps strength but is associated with changes in muscle activation patterns - Zhang, S.; Fu, W.; Xia, R.; Wang, X. (Isokinetics and Exercise Science, 2016)
BACKGROUND: The mechanism by which increased compression affects muscle strength and electromyographic (EMG) time/frequency domain behavior during prolonged muscle actions has yet to be elucidated. The mechanism by which increased compression affects muscle strength and electromyographic (EMG) time/frequency domain behavior during prolonged muscle actions has yet to be elucidated. OBJECTIVE: To determine the effectiveness of compression on quadriceps strength and endurance and EMG amplitude/frequency of the quadriceps during repeated concentric muscle contractions. To determine the effectiveness of compression on quadriceps strength and endurance and EMG amplitude/frequency of the quadriceps during repeated concentric muscle contractions. METHODS: Twelve healthy male athletes executed 25 maximal repeated isokinetic knee extensions in compression garment (CG) and control condition (CC) at 60 and 300°/s on a dynamometer. The EMG time and frequency domain behavior of the rectus femoris (RF), vastus lateralis (VL), and vastus medialis were collected synchronously. Twelve healthy male athletes executed 25 maximal repeated isokinetic knee extensions in compression garment (CG) and control condition (CC) at 60 and 300°/s on a dynamometer. The EMG time and frequency domain behavior of the rectus femoris (RF), vastus lateralis (VL), and vastus medialis were collected synchronously. RESULTS: Compression exerted no significant effect on peak moment and total work during the isokinetic contractions. By contrast, the overall EMG root mean square amplitude was significantly lower (p < 0.05) in CG than in CC while the EMG mean power frequency of the RF and VL was significantly higher (p < 0.05) in CG than in CC at 60°/s. Compression exerted no significant effect on peak moment and total work during the isokinetic contractions. By contrast, the overall EMG root mean square amplitude was significantly lower (p < 0.05) in CG than in CC while the EMG mean power frequency of the RF and VL was significantly higher (p < 0.05) in CG than in CC at 60°/s. CONCLUSION: The described effects may potentially improve muscle endurance and fatigue resistance during prolonged muscle actions. The described effects may potentially improve muscle endurance and fatigue resistance during prolonged muscle actions.